Erlangen pipe flow: the concept and DNS results for microflow control of near-wall turbulence - Lammers, Peter; Jovanovic, Jovan; Frohnapfel, Bettina; Delgado, Antonio (Microfluidics and Nanofluidics, 2012)
The concept of a micropatterned surface morphology capable of producing self-stabilization of turbulence in wall-bounded flows is considered in pipes of non-circular cross-sections which act to restructure fluctuations towards the limiting state where these must be entirely suppressed. Direct numerical simulations of turbulence in pipes of polygon-shaped cross-sections with straight and profiled sides were performed at a Reynolds number Res ' 300 based on the wall shear velocity and the hydraulic diameter. Using the lattice Boltzmann numerical algorithm, turbulence was resolved with up to 540 * 10 6 grid points (8;192 * 257 * 256 in the x 1, x 2 and x 3 directions). The DNS results show a decrease in the viscous drag around corners, resulting in a reduction of the skin-friction coefficient compared with expectations based on the wellestablished concept of hydraulic diameter and the use of the Blasius correlation. These findings support the conjecture that turbulence might be completely suppressed if the pipe cross-section is a polygon consisting of a sufficient number of profiled sides of the same length which intersect at right angles at the corners. © Springer-Verlag 2012.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.erlang